In memoriam - Professor Tony Wilkinson - Kennet, Derek; McCorriston, Joy (Proceedings of the Seminar for Arabian Studies, 2015)
It is a great sadness to have to record that Tony Wilkinson died on 25 December 2014. Tony was well known to all of those working on the archaeology of Arabia where he was a significant figure. He was a leading expert on Middle Eastern landscapes and was said to have ‘revolutionized our understanding of the ancient landscapes of Mesopotamia and the broader Middle East’ (Gil Stein). Much of this wider body of work has made an indirect but notable contribution to our understanding of Arabian landscapes, but he also conducted fieldwork specifically in Arabia, principally in Yemen but also in Oman early in his career, and briefly in Saudi Arabia on the Darb Zubaydah survey.